More than Mainstreaming : Promoting Gender Equality and Empowering Women through Post-Disaster Reconstruction - MDF-JRF Secretariat (World Bank, Jakarta, 2014)
The Multi Donor Fund for Aceh and Nias (MDF) and the Java Reconstruction Fund (JRF) have played significant roles in the remarkable recovery of Aceh, Nias and Java, following some of the worst disasters in Indonesia in recent years. The MDF and the JRF, which is patterned after it, are each considered a highly successful model for post-disaster reconstruction. This paper presents lessons from the MDF and JRF's efforts to facilitate women's empowerment and gender equality during the reconstruction process. The reconstruction process presented opportunity to address gender issues and other social inequalities. Enhancing the role of women under the MDF and JRF programs saw significant results, such as improved and sustained outcomes in housing and infrastructure, faster economic and livelihood recovery and increased productivity, strengthening of women's legal rights, more representative decision making and enhanced resilience for women and communities.